2001
DOI: 10.2460/ajvr.2001.62.1307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of equine immunoglobulin specific for Rhodococcus equi virulence-associated proteins A and C for use in protecting foals against Rhodococcus equi-induced pneumonia

Abstract: Degree of protection against R. equi-induced pneumonia provided by purified immunoglobulin specific for VapA and VapC was similar to that provided by commercially available HIP. Results not only suggest that immunoglobulin is the primary component of HIP that confers protection against R. equi-induced pneumonia in foals but also indicate that antibodies against R. equi VapA and VapC are protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 36 publications
1
51
0
3
Order By: Relevance
“…3) measure the ability of the organism to survive the innate immunity provided by macrophages. The observed attenuation of R. equi Ace-21 in these models was supported by infection studies with 3-week-old foals, in which the aceA mutant was found to be completely attenuated, since clinical and pathological findings were similar to those associated with infection of foals with a virulence plasmid-negative and therefore avirulent isolate (8,15).…”
Section: Discussionmentioning
confidence: 54%
“…3) measure the ability of the organism to survive the innate immunity provided by macrophages. The observed attenuation of R. equi Ace-21 in these models was supported by infection studies with 3-week-old foals, in which the aceA mutant was found to be completely attenuated, since clinical and pathological findings were similar to those associated with infection of foals with a virulence plasmid-negative and therefore avirulent isolate (8,15).…”
Section: Discussionmentioning
confidence: 54%
“…Although antibody provides partial protection against R. equi pneumonia (14), the role of the Ig isotype has not been described. Prescott et al determined that the antibody response of young foals to the APTX antigen with aluminium hydroxide adjuvant induced a more IgGb-and IgGT-biased subisotype response than did natural infection, which induced an IgGa-dominant response (30).…”
mentioning
confidence: 99%
“…Evidence for a role of antibody in protection against R. equi is the protective effect of passively transferred anti-R. equi hyperimmune equine plasma which is used extensively on endemically affected farms to reduce morbidity and mortality. Hooper-McGrevy et al [36] showed that purified VapA-and VapC-antibody provided protection of foals against experimental pneumonic infection equivalent to that obtained with hyperimmune plasma. Interestingly, however, foals born to vaccinated mares are not protected against infection despite passive transfer of R. equi antibody.…”
Section: Immunitymentioning
confidence: 97%